Analisis Undang-Undang Republik Indonesia Nomor 20 Tahun 2003 Tentang Sistem Pendidikan Nasional Terhadap Akses Orang Miskin pada Pendidikan - Rizki Nur Amalia; Heppy Hyma Puspytasari (Perspektif Hukum, 2018)
Government steps in realizing compulsory education is not only to provide and build infrastructure kepelosok education area, but the government is also expected to provide assistance in the form of program costs in order to support compulsory education. Investigators therefore conducted this research with the aim to determine the role of Law Number 20 Year 2003 on National Education System in protecting the rights of poor people to participate in education and to investigate the role of government in providing the poor access to education. The method used in this research is qualitative research and research sites located in Jombang District Education Office, SMA Patriot and SMA PGRI in the district Peterongan. Data collection techniques in this study through observation (participatory observation), interviews (structured interviews), documentation (research results). Results from the study showed that education in Jombang district is not discriminatory, even poor people get education services such as the PIP and BKSM budgeted from APBD and APBN.